Novel functional copolymer: Design, synthesis, click chemistry modification, and evaluation of dielectric and thermal properties - Yucel, Yunus; Koran, Kenan; Caliskan, Eray; Biryan, Fatih (Elsevier, 2025)
In this study, the modification of new polymers carrying dipeptide side groups with chalcone and their electrical properties were investigated. Therefore, initially, the phenylalanine dipeptide (Tyr(Boc)-Phe-OCH3) was synthesized. The ester group in the structure of this compound was converted to carboxylic acid to obtain the BocTyrosine Phenylalanine-OH (Tyr(Boc)-Phe-OH) compound. This compound reacted with propargyl amine (PA) to synthesize (Tyr(Boc)-Phe-PA), which subsequently reacted with methacryloyl chloride to produce the methacrylate monomer (MA-Tyr(Boc)-Phe-PA). The polymerization of the prepared methacrylate monomer was carried out using the free radical polymerization method. In the final step, the active alkyne-terminated homopolymer reacted with the azide-terminated (4-Cl-CF3 N3-Chalcone) under copper catalysis through a click reaction, resulting in the synthesis of poly(MA-Tyr(Boc)-Phe-click-chalcone). The thermal behaviors of the polymers were determined using DSC and TGA thermal analysis methods. The initial decomposition temperature of the polymer was found to be 207.05 degrees C, whereas this value was 188.53 degrees C for the P(MA-Tyr(Boc)-Phe-click-chalcone) polymer. Additionally, the temperatures corresponding to a 50 % mass loss were 383.79 degrees C for the P(MA-Tyr (Boc)-Phe-PA) polymer and 394.78 degrees C for the P(MA-Tyr(Boc)-Phe-click-chalcone) polymer. The dielectric constant of the P(MA-Tyr(Boc)-Phe-PA) polymer was calculated to be 8.98, while the dielectric constant of the modified polymer obtained after click modification was calculated to be 13.87. The increase in the dielectric constant is thought to be due to the greater polarization of the triazole ring formed by the click reaction under an electric field. Furthermore, the AC conductivities of the compounds were calculated to be 5.00 x 10-9 S/cm and 1.11 x 10-9 S/cm at 1 kHz. When the dielectric properties of these two compounds are compared, the second polymer exhibits better polarization in an electric field, indicating its potential use as an electronic circuit element.
Keywords: Dipeptide; Electrical property; Chalcone; Click chemistry; Polymer synthesis